Improving the Efficiency of the Personal Housing Loan Application Process through the Naval Service through Automation and Inclusive Socialization - Adi Saputra, Brian Winata; Syamsunasir (Dinasti Publisher, 2025)
Efficiency in the process of applying for personal housing loans through the Indonesian Navy is a strategic step to improve member welfare. This study examines the implementation of automation of the loan application system and inclusive socialization as an effort to accelerate the administrative process, increase transparency, and expand access to information to all members, including those in remote areas. Automation allows for the digitization of document submission, data integration between departments, and automatic notifications that speed up the process and minimize uncertainty. Meanwhile, inclusive socialization through face-to-face training, online seminars, and internal media ensures members understand the procedures and benefits of the program. The results of the study show that the synergy between automation and socialization improves service efficiency, transparency, and member satisfaction with the loan program. This approach also builds trust and awareness that the program supports welfare without discrimination. With effective implementation, this strategy is expected to increase member motivation and loyalty to the institution, while strengthening the economic stability of their families.